Factors associated with nurses' opinions and practices regarding information and consent. (May 2014) - Ingravallo, Francesca; Gilmore, Emma; Vignatelli, Luca; Dormi, Ada; Carosielli, Grazia; Lanni, Luigia; Taddia, Patrizia
This cross-sectional survey aimed to investigate nurses' opinions and practices regarding information and consent in the context of a large Italian teaching hospital and to explore potential influences of gender, age, university education, length of professional experience, and care setting. A questionnaire was administered to 282 nurses from six different care settings (Emergency Room, Emergency Medicine, Surgery, Hematology–Oncology, Geriatrics, and Internal Medicine). Overall, 84% (n = 237) of nurses returned the questionnaire (men: 24%; mean age: 36.2 ± 8 years; university degree: 35%; mean length of professional experience: 12 ± 8.2 years). Most respondents regularly informed patients about medications and nursing procedures and asked for consent prior to invasive procedures, but some provided information to relatives instead of patients. Lack of time or opportunity was the main difficulty in informing patients. The work setting was the foremost factor significantly associated with participants' opinions and practices. Further investigations are needed to confirm these findings in similar and other care settings.